2004
DOI: 10.1124/jpet.103.064956
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CXCR4 Receptor Dimerization by the Chemokine SDF-1α and the HIV-1 Coat Protein gp120: A Fluorescence Resonance Energy Transfer (FRET) Study

Abstract: Both the chemokine SDF-1␣ and the human immunodeficiency virus-1 (HIV-1) coat protein gp120 can bind to CXCR4 chemokine receptors but with different signaling consequences. To understand the molecular basis for these differences, we tagged the rat CXCR4 receptor with enhanced cyan (ECFP) and yellow (EYFP) derivatives of the green fluorescent protein and investigated CXCR4 receptor dimerization in human embryonic kidney (HEK)-tsA201 cells using fluorescence resonance energy transfer (FRET). Elevated FRET was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 42 publications
5
44
2
1
Order By: Relevance
“…One of the earliest events in HIV-1 NL4-3 infection is CXCR4-mediated activation of LIMK1 and cofilin phosphorylation; these events increase cortical actin dynamics in resting CD4 + T cells (27,32), a process that might require CXCR4 dimerization (53). Our data confirm these observations, because we detected rapid gp120 IIIB -mediated actin polymerization following transient LIMK1 activation and cofilin inactivation.…”
Section: Discussionsupporting
confidence: 81%
“…One of the earliest events in HIV-1 NL4-3 infection is CXCR4-mediated activation of LIMK1 and cofilin phosphorylation; these events increase cortical actin dynamics in resting CD4 + T cells (27,32), a process that might require CXCR4 dimerization (53). Our data confirm these observations, because we detected rapid gp120 IIIB -mediated actin polymerization following transient LIMK1 activation and cofilin inactivation.…”
Section: Discussionsupporting
confidence: 81%
“…The balance between homo-and heterodimers might therefore have a role in CXCL8 function; indeed, via CXCR1, CXCL8 selectively activates phospholipase D and the neutrophil respiratory burst (14,24), whereas CXCR2 is involved in CXCL8-mediated neutrophil migration (50). Cumulative evidence indicates that the dimerization of chemokine receptors should no longer be a matter of debate (4,5,7,10,12,51,52). Efforts should focus on studying the dynamics and functional relevance of receptor homo-and heterodimerization; understanding these concepts will change our view of chemokine receptor structure and activation, which is likely to have substantial influence on drug development and screening.…”
Section: Discussionmentioning
confidence: 99%
“…Several questions nonetheless remain to be answered, including the dynamic nature of receptor complexes and the role of ligands in promoting the conformational changes needed for function. The ligand must bind to chemokine receptors to activate them; some reports nonetheless claim no ligand effect on constitutively expressed dimers (6), whereas others show ligand-promoted complex stabilization (5,7). CXCL12 is reported to induce conformational changes in its receptor, CXCR4, and synthetic peptides of CXCR4 transmembrane domains inhibit receptor activation by blocking ligand-induced transition to the dimeric state (5).…”
mentioning
confidence: 99%
“…Additionally, a recent study in pre-B lymphocytes and breast carcinoma cells (Schabath et al, 2006) demonstrates that exclusion of CXCR4 from membrane lipid rafts, due to reduction in cholesterol levels, impairs the ability of CXCL12 to trigger cell motility via ERK phosphorylation and attenuates tumor growth. An intriguing alternative (that would also depend on colocalization of the two receptors in lipid rafts) is that stimulation with DAMGO or endomorphin-1 induces heterodimerization of MOR with CXCR4, leading to a reduced CXCL12 function as suggested by Fluorescence Resonance Energy Transfer (FRET) studies in cell lines (i.e., HEK293 cells) (Toth et al, 2004). Although CXCR4 receptors seem to exist primarily as homodimer, this study showed a specific association of CXCR4 with other GPCRs (namely μ-opioid, κ-opioid, and m3-muscarininc receptors) that could impair CXCR4 function.…”
Section: Discussionmentioning
confidence: 99%